Jembatan Bahasa dan Budaya: Implementasi Prinsip BIPA dalam Pembelajaran Anak Usia Dini di RA - Fitria Desiana Fatmawati; Ahmad Faizi; Resdianto Permata Raharjo (Mutiara Pendidikan dan Olahraga, 2026)
Indonesian for Foreign Speakers (BIPA) has developed not only as a language learning program for international learners but also as a medium for introducing Indonesian culture. In the context of early childhood education, BIPA principles can be adapted to support language acquisition and intercultural understanding among children in Raudhatul Athfal (RA). This study aims to analyze the implementation of BIPA principles in early childhood learning and examine their contribution to language development and cultural awareness. The study employed a qualitative descriptive approach through literature review and analysis of learning practices in early childhood education. The findings indicate that BIPA principles, including contextual learning, communicative interaction, cultural integration, and learner-centered instruction, can be effectively integrated into RA learning activities. Storytelling, songs, games, role-playing, and local cultural exploration facilitate children's language development while fostering positive attitudes toward cultural diversity. The integration of language and culture creates meaningful learning experiences and strengthens children's communicative competence from an early age. The study implies that adapting BIPA principles in RA can serve as an innovative strategy for developing language skills, cultural literacy, and social interaction competencies. Therefore, teachers need to design learning activities that integrate language use with cultural experiences in a developmentally appropriate manner.